Responses of ecosystem carbon cycle to experimental warming: a meta‐analysis. Issue 3 (1st March 2013) - Lu, Meng; Zhou, Xuhui; Yang, Qiang; Li, Hui; Luo, Yiqi; Fang, Changming; Chen, Jiakuan; Yang, Xin; Li, Bo
Abstract : Global warming potentially alters the terrestrial carbon (C) cycle, likely feeding back to further climate warming. However, how the ecosystem C cycle responds and feeds back to warming remains unclear. Here we used a meta‐analysis approach to quantify the response ratios of 18 variables of the ecosystem C cycle to experimental warming and evaluated ecosystem C‐cycle feedback to climate warming. Our results showed that warming stimulated gross ecosystem photosynthesis (GEP) by 15.7%, net primary production (NPP) by 4.4%, and plant C pools from above‐ and belowground parts by 6.8% and 7.0%, respectively. Experimental warming accelerated litter mass loss by 6.8%, soil respiration by 9.0%, and dissolved organic C leaching by 12.1%. In addition, the responses of some of those variables to experimental warming differed among the ecosystem types. Our results demonstrated that the stimulation of plant‐derived C influx basically offset the increase in warming‐induced efflux and resulted in insignificant changes in litter and soil C content, indicating that climate warming may not trigger strong positive C‐climate feedback from terrestrial ecosystems. Moreover, the increase in plant C storage together with the slight but not statistically significant decrease of net ecosystem exchange (NEE) across ecosystems suggests that terrestrial ecosystems might be a weak C sink rather than a C source under global climate warming. Our results are also potentially useful for parameterizing and benchmarking land surface models in terms of C cycle responses to climate warming.